Digestive Physiology and Nutritional Responses of Autographa gamma (L.) (Lepidoptera: Noctuidae) on Different Sugar Beet Cultivars. Issue 1 (20th June 2016) - Naseri, Bahram; Golikhajeh, Neshat; Rahimi Namin, Foroogh
Abstract: Digestive enzymatic activity and nutritional responses of Autographa gamma (L.) (Lepidoptera: Noctuidae), an important insect pest of sugar beet, on nine sugar beet cultivars (Peritra, Karolina, Paolita, Lenzier, Tiller, Ardabili, Persia, Rozier, and Dorothea) were studied. The highest proteolytic activity of fourth and fifth instar of A. gamma was in larvae fed on cultivar Persia. The highest amylolytic activity of fourth and fifth instar was observed in larvae fed on cultivars Rozier and Dorothea, respectively. The lowest proteolytic and amylolytic activities in fourth instar were observed on cultivar Tiller; whereas the lowest activities in fifth instar were detected on cultivars Karolina and Tiller, respectively. Larval weight in both larval instars (fourth and fifth) was the heaviest on cultivar Persia and the lightest on cultivar Karolina. Furthermore, weight gain of larvae was the highest on cultivar Persia and the lowest on cultivar Karolina. The results of this study suggest that cultivar Tiller was the most unsuitable host plant for feeding of A. gamma .